BELA NEGARA SEBAGAI PENGEJAWANTAHAN DALAM KETAHANAN NASIONAL BERDASARKAN UUD NRI 1945 - Luh Suryatni (JURNAL ILMIAH HUKUM DIRGANTARA, 2019)
Abstract :State defense and national resilience have a very tight relationship in realizing the country objectives as stated in the opening of the 1945 Constitution of the Republic of Indonesia in paragraph IV. State defense as an effort to protect the country through the determination, attitude and spirit also actions of all citizens in a regular and integrated manner which is imbued by the Unitary State of the Republic of Indonesia based on the Pancasila and the 1945 Constitution of the Republic of Indonesia. Likewise with national resilience, which is a dynamic condition of the nation based on the  tenacity and resilience that contains the ability to develop national strength and overcome all forms of challenges, threats, obstacles, and disturbances, both coming from inside and outside, directly or indirectly, which can endanger the integrity in realizing the country objectives. Therefore, national resilience is a strategy to defend and protect the country. The purpose of this paper is to find out the importance of state defense and national resilience in realizing the country objectives. The data collection method used is a literature review with descriptive analysis techniques. The results of the study showed that state defense and national resilience have a connection in realizing the country objectives through the process of character building in the social, nation and state life. Keywords: State defense, national resilience and the 1945 Constitution of the Republic of Indonesia